(untitled) (LEARNing Landscapes, 2013)
A growing hope is that Twitter and similar technologies will enhance teachers’ professional growth by allowing them to collaborate and support each other online. In this conceptual paper, we evaluate the potential of such claims, theorizing about the relationships among technologies, practice, and communities of practice. Specifically, we demonstrate how the concepts of materiality and sociomateriality can be applied toward understanding and researching teachers’ professional communities on Twitter. Materiality refers to the physical or digital components of a technology. Sociomateriality refers the social practices and contexts shaping one’s sense of a technology.